Corpos líquidos: circulação de nudes em jovens usuários de redes sociais e o psicodrama junguiano - Cardoso Júnior, Aroldo de Lara (2021)
Nudes have become Internet practices, widely called sexting, which are embedded in love relationships. This research aims to investigate these practices and their possible sufferings, relating Problematic Internet Use with the circulation of nudes as a starting point for the investigation of possible suffering. Recruitment for the survey was conducted over the Internet with young people aged 18-26. Social networks (Facebook, Instagram) and relationship apps (Grindr, Her) were used. Creswell's (2010) method was used in the construction of mixed methods research. An online questionnaire and the Internet Addiction Test were applied to 94 participants. An online jungian psychodrama session with two participants and an auxiliary ego followed. Quantitative data were analyzed using IBM's SPSS software, qualitative information from the online questionnaire was subject to categorization, and the jungian psychodrama session was subject to thematic and symbolic analysis. The results showed a negative correlation between the result of the Internet Addiction Test and satisfaction with one's nudes, a positive correlation between frequency of access to pornography and frequencies of sending, receiving and unsolicited receiving, and negative correlations between risk perception and the frequency of sending nudes and between risk perception and satisfaction with one’s nudes. The discourses point to eroticism as a motivation for practice, to the relationship between nudes and body satisfaction, to risks of exposure over the Internet, with a feeling of pressure in the behavior of sending nudes, and reporting of suffering such as the feeling of pressure for the approval of the other, condition of sociability, adequacy to bodily standards and fear of undue exposure. The continuity of research on the subject in Brazil is indicated